GANGGUAN POLA TIDUR PADA REMAJA GAMING DISORDER - Rendi Ariyanto Sinanto; Fatwa Tentama; Sitti Nur Djannah; Astry Axmalia (Dian Nuswantoro Semarang, 2021)
Addiction to online games can alter sleep patterns, which can put your health at risk. This study aims to determine how the sleep patterns of gaming disorder students. This study uses a qualitative design with a phenomenological approach, involving six participants with a purposive sampling technique and collecting data using interviews and observation. The credibility of data using member check and triangulation method, then using phenomenological analysis. While playing online games, all participants often stayed up late to be exhausted due to lack of sleep, then slept only during the day, felt dizzy, and disturbed concentration. Then all participants did not want to leave the game because they were not satisfied and could not control themselves. All participants experienced game addiction in the high category (100%) and a hobby of playing games. There are disturbances in sleep patterns due to playing online games, such as staying up late. Participants are expected to prioritize physical needs such as sleep rest and limit the hours of playing games to a maximum of two hours a day to reduce the risk of harmful health effects.Keywords: Sleep Pattern Disorder, Gaming Disorder, Student